A review on thermophysical properties of nanofluids and heat transfer applications. (July 2017) - Gupta, Munish; Singh, Vinay; Kumar, Rajesh; Said, Z.
Abstract: This paper summarizes the important results regarding the improvement in the thermophysical properties of nanofluids. The influence of important parameters like particle's (loading, material, size, and shape), base fluid type, temperature, additives and pH value has been considered. There are many conflicting reports on the influence of parameters on thermophysical properties and the literature in this field is widespread, so this article would be beneficial for investigators to have a precise screening of a broad range of studies in this field. Further literature review of the applications of nanofluids with a particular focus on the advantages of using nanofluids in solar collectors and as coolants in automotive heat exchangers. The authors hope that this review can help in the translation of nanofluid technology from the lab scale research to industrial applications in solar collectors and automotive sector. At last, the paper identifies the opportunities for future research.